THE IMPACT OF INDUSTRIAL PLACEMENT ON STUDENTS’ EMPLOYABILITY SKILLS IN TERTIARY EDUCATION - Betchoo, Nirmal Kumar (PEOPLE: International Journal of Social Sciences, 2017)
This research aims at assessing the impact of industrial placement on students’ employability skills in the tertiary education sector in Mauritius. Long-time neglected and considered as accessory to academic learning, industrial placement is nowadays a necessity for this category of students. In a competitive world where there needs be a suitable match between employment skills and job demands, industrial placement is rightly considered as a stepping stone to the forthcoming work-life career of the individual. The research states that students undergoing industrial placement in suitable companies learn the various skills and techniques in a job environment, gain greater confidence and maturity prior to embarking on a job. This study is limited to a sample of students from Université des Mascareignes that has formalised such training using an established methodology and framework to assess students. It is clearly approved that industrial placement is relevant in tertiary academic learning in that it bridges the gap between school and the immediate work environment.